Tetal. Tribe Pod / Haritz Aiman Arman - Arman, Haritz Aiman (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
This tribe pod is inspired from the Tetal or fire place in Kelabit longhouse. The reason is that the Tetal function as beacon for the families to be together. The same goes to my tribal pad concept which is to expose visual interaction and the idea is to replicate social interaction of Kelabit tribe.